2017
DOI: 10.1016/j.jid.2017.02.975
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Financial Burden of Atopic Dermatitis in the United States

Abstract: Little is known about the inpatient burden of atopic dermatitis (AD). We sought to determine the risk factors and financial burden of hospitalizations for AD in the United States. Data were analyzed from the 2002-2012 National Inpatient Sample, including a 20% representative sample of all hospitalizations in the United States. Hospitalization rates for AD or eczema were highest in the northeast during the winter and south during the summer. Geometric mean cost of care (95% confidence interval) was lower for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
3
37
1
3
Order By: Relevance
“…There are very few visits in December for AD, and other social and holiday events may modulate the number of observed visits in this month. Again, as previously stated, US hospitalization rates for AD were highest in the Northeast US during the winter and south during the summer . However, in Denmark, healthcare utilization was highest in the winter and spring .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…There are very few visits in December for AD, and other social and holiday events may modulate the number of observed visits in this month. Again, as previously stated, US hospitalization rates for AD were highest in the Northeast US during the winter and south during the summer . However, in Denmark, healthcare utilization was highest in the winter and spring .…”
Section: Discussionsupporting
confidence: 73%
“…This author has spent nearly all of his practicing career in the American South, the warmest overall region in the US, and had first‐hand experience with patient flares occurring in the summer months. Supporting the notion that summer and/or high temperatures may play a role in disease exacerbation, by examining US healthcare expenditures, Silverberg and colleagues found that hospitalization rates for AD were highest in the Northeast US during the winter and South during the summer …”
Section: Discussionmentioning
confidence: 99%
“…Pruritus, a hallmark of AD, can lead to skin damage as patients may scratch until bleeding excoriations result, which further aggravates the disease . Furthermore, AD is primarily a chronic, relapsing and lifelong condition for patients, and causes a substantial economic burden in addition to the disease burden . In 2014, the total number of patients with AD receiving treatment in Japan was estimated to be 456 000 according to the figures reported by the Ministry of Health, Labor and Welfare…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, AD is primarily a chronic, relapsing and lifelong condition for patients, and causes a substantial economic burden in addition to the disease burden. 4 In 2014, the total number of patients with AD receiving treatment in Japan was estimated to be 456 000 according to the figures reported by the Ministry of Health, Labor and Welfare. 5 The complicated interaction among genetics, environmental factors, impaired skin barrier and immunological abnormality probably contributes to the development of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD) constitutes the most prevalent chronic condition in infancy and causes significant morbidity and burden for patients, their families and healthcare systems . Epidemiologic studies indicate that AD is not only associated with other atopic conditions, but also with a broad spectrum of other chronic conditions .…”
Section: Introductionmentioning
confidence: 99%